Macronyssus ellipticus - Orlova, Maria V.; Anisimov, Nikolay V. (Zenodo, 2023)
Macronyssus ellipticus (Kolenati, 1856) Distribution – Europe (Radovsky 1967), Russia (Stanyukovich 1997). Hosts – Myotis nattereri and My. myotis (Radovsky 1967; Haitlinger 1978), My. blythi (Orlova et al. 2015a), My. mystacinus , My. brandtii , My. dasycneme and My. daubentonii (Haitlinger 1978), My. sibiricus (Orlova et al. 2017a), Rhinolophus ferrumequinum and R. hipposideros (Stanyukovich 1997), Plecotus auritus (Radovsky 1967; Haitlinger 1978), Murina hilgendorfi (Orlova et al. 2015a). Published as part of Orlova, Maria V. & Anisimov, Nikolay V., 2023, Three new species of bat-parasitic gamasid mites of the genera Spinturnix, Macronyssus and Steatonyssus (Acari: Mesostigmata: Spinturnicidae, Macronyssidae) from Siberia and Mongolia, with keys to species of Russia and adjacent countries, pp. 211-239 in Persian Journal of Acarology 12 (2) on page 224, DOI:10.22073/pja.v12i2.76740, http://zenodo.org/record/8113590